Contribution to the study of the physiology of the Andean - calcemia and autonomic nervous system in the Andean highlands - Palti, Víctor (1939)
The study of Physiology Andino, initiated by Professor Monge in 1927, and continued by eminent national researchers, is one of the major research topics in the country.